The Acadian plutonic rocks of New Brunswick - Fyffe, L.; Pajari, G.; Cherry, M. (Atlantic Geology)

(untitled) (Maritime Sediments Editorial Board, 1981)
ABSTRACT Extensive blmodal plutonlam accompanied and followed Che Acadian deformation In New Brunswick. These Acadian plutona define a Central Plutonic Belt, which Is largely confined to a terrain with an Acadian trend of 030*, and a Southern Plutonic Belt, which occurs within a structural province with an Acadian and Varlscan trend of 060". It has been possible to classify the Acadian plutona north of the Avalonian Platform according to their structures, textures, field relationships, mineralogy, and chemical characteristics; supplemented by radiometric age dates. Plutonic rock types include: A-B a mafic-felalc association; C - syntectonic conallte and granodlorite; D - suacovlte-bearing; F - megacrystic granitoid*; H - equigranular blotlte granites; and E and G - 'transitional' granites. The magmatiam, regardless of location, follows a common evolutionary trend and appears to comprise a sequence of intrusions from early Devonian to Carboniferous time with no significant break in the evolution. These characteristics along with the blmodal chemistry and the lack of compositional polarity suggest that the development of these Acadian plutona was not subductloa-related. A time-dependent process such as radioactive heating of a thickened crust is a more probable mechanism for their genesis.